2013
DOI: 10.1186/1756-0500-6-240
|View full text |Cite
|
Sign up to set email alerts
|

Synovial sarcoma presenting with huge mediastinal mass: a case report and review of literature

Abstract: BackgroundSynovial sarcoma presenting in the mediastinum is exceedingly rare. Furthermore, data addressing optimal therapy is limited. Herein we present a case where an attempt to downsize the tumor to a resectable state with chemotherapy was employed.Case presentationA 32 year female presented with massive pericardial effusion and unresectable huge mediastinal mass. Computed axial tomography scan - guided biopsy with adjunctive immunostains and molecular studies confirmed a diagnosis of synovial sarcoma. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Soft tissue sarcoma is a rare malignancy, comprising less than 1% of malignant neoplasms; this proportion may be much less (<0.01%) in the thorax (6). In a previous study, synovial sarcoma was reported to account for 5% of 12,370 primary soft tissue sarcomas (7).…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue sarcoma is a rare malignancy, comprising less than 1% of malignant neoplasms; this proportion may be much less (<0.01%) in the thorax (6). In a previous study, synovial sarcoma was reported to account for 5% of 12,370 primary soft tissue sarcomas (7).…”
Section: Discussionmentioning
confidence: 99%
“…Complete tumor resection is the only therapy associated with long-term survival with uncertainty existing regarding the best therapeutic strategy for patients with unresectable disease. [2] External beam radiotherapy and chemotherapy are other therapeutic options that have been used as primary therapy mostly in an attempt to reduce the tumor size to achieve resectability. [2] Therapeutic combinations of surgery, chemotherapy, and radiotherapy have been used in the management of this neoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…[2] External beam radiotherapy and chemotherapy are other therapeutic options that have been used as primary therapy mostly in an attempt to reduce the tumor size to achieve resectability. [2] Therapeutic combinations of surgery, chemotherapy, and radiotherapy have been used in the management of this neoplasm. Here, we report a case of this rare tumor and review the relevant literature.…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant chemotherapy was administered to 12 adult patients (13.8%) and had no impact on survival [16]. Only few reports (case reports of adult patients with initially localized as well as initially metastatic SS) exist considering OS [19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%